Dealing with land-based marine pollution in Malaysia: A refelction on environmental law - Mustafa, Maizatun; Sufian, Azlinor (2010)
This paper discusses sources of land-based marine pollution in Malaysia specifically from point-sources, and examines existing provisions under domestic law relevant to the control of such pollution. Land-based pollutants, including that from point-sources, are known to be major contributors towards marine pollution in Malaysia. Over the years, expansion of economic development along the coastal areas, in addition to increasing population and urbanization, have further contributed towards the pollution of marine environment requiring effective measures to deal with the problem. In this regard, environmental law can play its role particularly in controlling pollution and protecting the quality of marine environment. For this purpose this paper seeks to examine the Environmental Quality Act 1974 which is considered as the most comprehensive environmental legislation in Malaysia on pollution control. This paper focuses on strategies introduced under this Act towards effective control of land-based point sources pollution for the purpose of marine environmental protection.